The Risk Factors and Incidence of Perineal Tears among Pregnant Women - Hafsa Mubashir, Nosheen Bano, Ayesha Naeem, Nazia Tufail, Sadia Shafiq, Anum Arooj (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the risk factors and prevalence of perineal tear in low-risk pregnant females. Study Design: A retrospective cross-sectional study. Place and Duration: In the Obstetrics and Gynecology department of Khawaja Muhammad Safdar Medical College, Allama Iqbal Memorial Teaching Hospital Sialkot for one-year duration from January 2020 to December 2020. Methods: The females with perineal tear after birth included in this study. A total of 400 females were selected for this study. Results are articulated as adjusted odds ratio (OR) and ​​<0.05 of P value is considered significant. Results: 400 total females had singleton vaginal delivery and perineal tears were noticed in 140 females. The episiotomy frequency for the total of 1st and 2nd degree, and 3rd and 4th degree (OASI) were 16.3%, 25%, and 1.5%, correspondingly. The perineal tear risk-factors are young mothers (teenagers OR = 5.6, 21-25 years OR = 4.3), primiparous women (OR = 12.6), gestational age less than 32 weeks OR = 0.175), received antenatal care (OR = 0.42), correspondingly. Primiparous females were 12.4 times more probable to have an episiotomy (OR = 12.4, 95% CI, 1.48-104.8, p = 0.02). A birth weight between 2.5-3.0 kgs and less than 2.5 kg (OR = 0.012 and 0.084, respectively) protects against Obstetric Anal Sphincter Injury. Conclusions: The perineal injuries risk factors are comparable to those formerly described in other researches. There is an urgent need to train the gynae staff and doctors in proper selection for episiotomy and better perineal care in order to improve obstetric services in the Gynecology department. Identifying those at danger can decrease obstetric perineal injuries. Keywords: Low risk pregnancy, episiotomy, low-risk pregnancy and Obstetric Anal Sphincter Injury.